Unsur Supranatural Dalam Teks Lamut “Kerajaan Palinggam” - Irni Cahyani (Jurnal Hadratul Madaniyah, 2018)
Supernatural is above natural things, where supernatural is more aimed at natural phenomenon and is kebatinan culture / world. While the lamut is an oral literature performed by a single player (palanutan). The single player brings a certain story through the speech which in certain parts of his speech accompanied by a wasp of tarbanglamut. In this study, researchers examined the supernatural element in the text of the lamut "Palinggam Kingdom." This analysis yields the conclusion that the characters in the lamut text "Palinggam Kingdom" have supernatural powers, among others: 1) can transform themselves into birds, white walut, snakes, parents, mountains, beetles, and children; 2) can fly; 3) can make a very large boat of Balimbur Dragon; 4) can turn hair into arrows; 5) can stop the winds; 6) can make the god fall in the palm of the hand; 7) may disappear; 8) can rule the eagle; 9) can fight dragons, and 10) can kill giants.